1997
DOI: 10.1093/her/12.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of socioeconomic status for adolescents: the WHO Health Behaviour in School-aged Children Survey

Abstract: Many indicators of socioeconomic status used for adults are inappropriate for use in research on adolescents. In a school-based survey of 4079 Scottish schoolchildren using a self-completion questionnaire, over 20% of 11-15 year olds were unable to provide a substantive response on father's occupation. In contrast, indicators derived to construct a family affluence scale, which included car ownership, telephone ownership and the child having their own unshared bedroom, resulted in a 98% response rate; and 92% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
508
1
19

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 604 publications
(540 citation statements)
references
References 11 publications
12
508
1
19
Order By: Relevance
“…It has been proven to be useful in this age group as many adolescents are unable to provide information on their parents' occupation and income (23) . The amenities Table 4a Multivariate linear regression models of the relationship between sociodemographic characteristics and food scores in a sample of Palestinian adolescents in Ramallah, Nablus and Hebron governorates (n 2952)-Animal food score--Dairy products scorey Western food scoreJ Sweets and salty snacks scorez -The regression models are age adjusted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven to be useful in this age group as many adolescents are unable to provide information on their parents' occupation and income (23) . The amenities Table 4a Multivariate linear regression models of the relationship between sociodemographic characteristics and food scores in a sample of Palestinian adolescents in Ramallah, Nablus and Hebron governorates (n 2952)-Animal food score--Dairy products scorey Western food scoreJ Sweets and salty snacks scorez -The regression models are age adjusted.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used measures of social class in epidemiological study are occupation, education and income (Liberatos et al, 1988), but it is reported that in regard Food habits of Chinese adolescents Z Shi et al to self-administered questionnaires to adolescents, a large percentage are unable to provide a substantive response on father's occupation (Currie et al, 1997). Under these circumstances, the WHO Health Behaviour in School-aged Children Survey adopted the 'family affluence scale' as an additional indicator of SES based on household possessions (Currie et al, 1997(Currie et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Under these circumstances, the WHO Health Behaviour in School-aged Children Survey adopted the 'family affluence scale' as an additional indicator of SES based on household possessions (Currie et al, 1997(Currie et al, , 2004. The same approach has also been used in developing countries (Durkin et al, 1994;Stene et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SES was assessed using the Family Affluence Scale [51]; the scale ranged from 0 to 9, with higher scores indicating greater SES. The low self-control scale, a previously validated scale [52] widely used in the criminology literature, ranged from 1 to 3, with higher scores indicating lower self-control.…”
Section: Methodsmentioning
confidence: 99%